2021
DOI: 10.1053/j.gastro.2020.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial TLR4 Signaling Activates DUOX2 to Induce Microbiota-Driven Tumorigenesis

Abstract: BACKGROUND & AIMS: Chronic colonic inflammation leads to dysplasia and cancer in patients with inflammatory bowel disease. We have described the critical role of innate immune signaling via Toll-like receptor 4 (TLR4) in the pathogenesis of dysplasia and cancer. In the current study, we interrogate the intersection of TLR4 signaling, epithelial redox activity, and the microbiota in colitisassociated neoplasia. METHODS: Inflammatory bowel disease and colorectal cancer data sets were analyzed for expression of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 56 publications
(70 reference statements)
2
49
1
1
Order By: Relevance
“…Recently, a report showed the intersection of TLR4 signaling, epithelial redox activity and the microbiota in colitis-associated neoplasia. It was found that colonic epithelial cells (CECs) respond to Gram-negative bacterial challenge by inducing DUOX2-mediated release of ROS in a TLR4-dependent fashion [ 40 ]. In summary, NOX enzymes act downstream of TLRs signaling pathway, which are associated with ROS generation ( Figure 1 ).…”
Section: Oxidative Stress Mediated By Prr-dependent Pathwaysmentioning
confidence: 99%
“…Recently, a report showed the intersection of TLR4 signaling, epithelial redox activity and the microbiota in colitis-associated neoplasia. It was found that colonic epithelial cells (CECs) respond to Gram-negative bacterial challenge by inducing DUOX2-mediated release of ROS in a TLR4-dependent fashion [ 40 ]. In summary, NOX enzymes act downstream of TLRs signaling pathway, which are associated with ROS generation ( Figure 1 ).…”
Section: Oxidative Stress Mediated By Prr-dependent Pathwaysmentioning
confidence: 99%
“…DMBT1 gene, which is considered as a candidate tumor suppressor gene for the brain, lungs, stomach, and colorectal cancers, has shown an increased expression in inflamed tissues of IBD patients, and it has been stated that impaired DMBT1 function may be associated with the onset of Crohn's disease (Renner et al, 2007). Moreover, polymorphisms/mutations of Toll-like receptors (TLR), which are innate immune receptors, have been directly linked to IBD (Lu et al, 2018), and activation of epithelial TLR4 in IBD and colorectal cancer has been associated with upregulation of DUOX2 (Burgueño et al, 2020). It has been reported that MARK2, a master regulator of cell polarity in intestinal epithelial cells, may contribute to the initiation and progression of IBD by interfering with the protein kinase cascade (Yuan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In our data, HCE cells significantly upregulated UBD in response to F. nucleatum exposure. DUOX2 is upregulated in inflammatory bowel disease and colorectal cancers and, alongside DUOXA2 , is a primary driver of H 2 O 2 production in mucosal tissues, which may contribute to chronic inflammation and reactive oxygen species (ROS)-related DNA damage ( 74 , 75 ). DUOX2 and DUOXA2 were both strongly upregulated by HCE cells in response to F. nucleatum , suggesting that F. nucleatum may drive H 2 O 2 production in the setting of the colon.…”
Section: Discussionmentioning
confidence: 99%